(untitled) (Research, Society and Development, 2022)
Insect vectors of Leishmaniases, Chagas disease and African trypanosomiasis remain human health, veterinary and economic problems worldwide. Several sex pheromones molecules that contribute to mating behavior have been identified in these vectors. These chemical signals are potential alternatives to traditional chemical insecticides. This review discusses the diversity of sex pheromone molecules and their role in the mating behavior of insect vectors of Leishmaniases, Chagas disease and African trypanosomiasis. The selection of studies was made based on research and review articles that presented sex pheromone aspects regarding insect vectors. In some species, these molecules have a dual function as serving as sex and aggregation pheromone. We also highlight the current knowledge of these substances as potential vector control tools. The studies revealed that sex pheromones applicability is largely experimental and restricted to some vectors. Based on these limitations, we included updated tables with the chemical identity of several sex pheromone compounds and other relevant information concerning the target species, which can contribute to future studies of control methodologies.